A Review: Metabolism of Lipid Via TREM-2A - Otitoju, Olawale; Iruka, Assumpta; Danjuma, Janya (Kwaghe International Journal of Sciences and Technology, 2024)
This review investigated the metabolism of lipid via TREM-2. Lipid metabolism is the synthesis and degradation of lipids in cells, involving the breakdown and storage of fats for energy and the synthesis of structural and functional lipids, such as those involved in the construction of cell membranes. Lipid metabolism is often considered as the digestion and absorption process of dietary fat; however, there are two sources of fats that organisms can use to obtain energy: from consumed dietary fats and from stored fat. Triggering receptor expressed on myeloid cells 2 (TREM-2) is a membrane receptor on myeloid cells and plays an important role in the body’s immune defense. Recently, TREM-2 has received extensive attention from researchers, and its activity has been found in Alzheimer’s disease, neuroinflammation, and traumatic brain injury. The appearance of TREM-2 is usually accompanied by changes in apolipoprotein E (ApoE). Apolipoprotein E (ApoE) is a protein playing a pivotal role in lipid homeostasis since it regulates cholesterol, triglyceride and phospholipid metabolism in the blood and the brain. APOE gene regulates the expression of this protein and has three different alleles: ε2, ε3 and ε4. Carrying an APOE4 allele is recognized as a genetic risk factor of late-onset Alzheimer's disease (LOAD) and coronary heart disease (CHD). A major function of apoE is to mediate the binding of lipoproteins or lipid complexes in the plasma or interstitial fluids to specific cell-surface receptors. These receptors internalize apoE-containing lipoprotein particles; thus, apoE participates in the distribution/redistribution of lipids among various tissues and cells of the body. It is likely that apoE, with its multiple cellular origins and multiple structural and biophysical properties, is involved widely in processes of lipid metabolism and neurobiology, possibly encompassing a variety of disorders of neuronal repair, remodeling, and degeneration by interacting with different factors through various pathways.